ERP Effects of Malicious Envy on Schadenfreude in Gain and Loss Frames - Lin, Huiyan; Liang, Jiafeng (Frontiers in Human Neuroscience, 2021)
Previous behavioral and neural studies have shown the effects of malicious envy on schadenfreude. However, it is unclear whether these effects are modulated by contextual frames (e.g., gain and loss frames). Thus, the present study aimed to investigate whether behavioral and event-related potential (ERP) effects of malicious envy on schadenfreude were different in gain and loss frames. To address this issue, participants in the present study believed they were playing a monetary game with several other players. In the malicious envy condition, participants won less money than the player in the gain frame and lost more money in the loss frame; in the control condition, both participants and the player gained little money in the gain frame and lost much in the loss frame. Subsequently, participants were informed that the player encountered a misfortune, i.e., gained little in the gain frame and lost much in the loss frame. Results showed that malicious envy increased feelings of schadenfreude and ERP responses when the player encountered a misfortune. Moreover, increased ERP responses by malicious envy occurred at the feedback-related negativity (FRN) and early late positive potential (LPP) time ranges in the gain frame but at the late LPP time range in the loss frame. The findings might suggest that malicious envy affects schadenfreude and corresponding neural activity, whereas the neural effects occur at comparatively early time ranges in the gain frame but at a later time range in the loss frame.